2016
DOI: 10.1371/journal.pone.0156831
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Body Size and Parasitic Fitness and Offspring Performance of Sclerodermus pupariae Yang et Yao (Hymenoptera: Bethylidae)

Abstract: The relationship between body size and fitness in parasitoid wasps has several effects on parasitic ability, reproductive behavior in female wasps, and progeny fitness. Female wasps with various body sizes were obtained by mass–rearing a gregarious ectoparasitoid, Sclerodermus pupariae, which is one of the excellent parasites to control the larvae and pupae of Buprestidae and Cerambycidae. We investigated the effects of body size of adult females introduced on Thyestilla gebleri (Coleoptera: Cerambycidae) larv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…Gao et al. () reported that when the parasitoid Sclerodermus pupariae Yang & Yao (Hymenoptera: Bethylidae) encountered bigger or more active hosts, large females had greater advantages to subdue host larvae than the smaller sized females. Moreover, the same authors found that generally, large female parasitoids have greater reproductive potential because of larger volume of the spermatheca than small females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gao et al. () reported that when the parasitoid Sclerodermus pupariae Yang & Yao (Hymenoptera: Bethylidae) encountered bigger or more active hosts, large females had greater advantages to subdue host larvae than the smaller sized females. Moreover, the same authors found that generally, large female parasitoids have greater reproductive potential because of larger volume of the spermatheca than small females.…”
Section: Discussionmentioning
confidence: 99%
“…The fitness of a female parasitoid positively influences the success of host parasitism. Gao et al (2016) reported that when the parasitoid Sclerodermus pupariae…”
Section: Discussionmentioning
confidence: 99%
“…These transcripts encode neurohormones, that is, proteins with functions in biosynthesis of ecdysone, metabolism of juvenile hormone, or chitin metabolism. They also found that two teratocyte proteins shared similarities with venom components, and two defensins exhibit anti-microbial activity which probably provide immune protection in the host-parasitoid system (Gao F et al 2016).…”
Section: Research Progress Of Parasitoid-host Interactionmentioning
confidence: 95%
“…Sclerodermus pupariae Yang et Yao (Hymenoptera: Bethylidae) is a newly discovered native gregarious idiobiont ectoparasitoid of the emerald ash borer (EAB), Agrilus planipennis Fairmaire (Coleoptera: Buprestidae), and an excellent parasitoid of larval and pupal Buprestidae and Cerambycidae (Yang et al 2012;Gao S et al 2016). The control efficiency of the bethylid parasitoids in suppression of wood-borers has been investigated in several wasp-host systems, especially S. pupariae (Gao S et al 2016;Gao S K et al 2016;Wang et al 2016;Wei et al 2016Wei et al , 2017. Parasitism and emergence rate in laboratory can be as high as 100% when the ratio of parasitoid-to-host is 1:1 while the rate in the field was 13% (Wei et al 2016).…”
Section: Biological Control Using Parasitoid Wasps In Other Agroecosymentioning
confidence: 99%
See 1 more Smart Citation